2019
DOI: 10.1186/s13104-019-4833-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving selectivity of DNA–RNA binding zinc finger using directed evolution

Abstract: ObjectiveType C2H2 zinc fingers bind a variety of substrates, specific sequences in the double-stranded DNA counting among them. Engineering efforts led to the discovery of a set of general rules that enable obtaining zinc fingers modules that bind to almost any given sequence. The objective of this work was to determine an analogical set of rules for the binding of specific sequences in DNA–RNA hybrids using directed evolution of ZfQQR zinc finger. The target regions for evolution included the amino acid resi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Numerous studies have reported that ZnF containing proteins are generally involved in protein–protein, protein-DNA, and protein-RNA interactions (Eom et al . 2016 ; Sulej 2019 ). To the best of our knowledge, the biochemical function of nsp2 is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that ZnF containing proteins are generally involved in protein–protein, protein-DNA, and protein-RNA interactions (Eom et al . 2016 ; Sulej 2019 ). To the best of our knowledge, the biochemical function of nsp2 is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…S9.6 is commonly used to detect and characterize R-loops in situ [12][13][14] and to obtain genome-wide R-loop sequence profiles [15,16]. Other hybrid binders include a protein based on the Zinc finger motif [17], and a neomycin-methidium conjugate binds hybrids in a sequence-nonspecific manner, forming complexes with sub-nanomolar (K D ) affinities [18].…”
mentioning
confidence: 99%